Restrictions on Judicial Review Rights for State Administrative Officials: A Critical Perspective on Constitutional Court Deci-sion No. 24/PUU-XXII/2024 - Annisa Dwi Lestari; Taufiqurrohman Syahuri; Ahmad Ahsin Thohari (International Journal of Law, Crime and Justice, 2025)
Restricting judicial review (peninjauan kembali) for state administrative officials through Constitutional Court Decision No. 24/PUU-XXII/2024 represents a pivotal shift in Indonesia’s administrative justice framework. This study critically examines the constitutional, theoretical, and comparative dimensions of that decision, situating it within the principles of equality before the law and due process enshrined in the 1945 Constitution. Employing a normative-qualitative design grounded in doctrinal analysis and comparative law methods, the research analyzes primary sources including the 1945 Constitution, Law No. 5 of 1986 on State Administrative Courts, Law No. 14 of 1985 on the Supreme Court, and the Constitutional Court’s decision and is supplemented by relevant academic literature. Findings reveal that the decision undermines procedural equality by asymmetrically restricting state entities’ access to extraordinary remedy mechanisms without addressing systemic enforcement deficiencies. Comparative analysis with French, German, and Thai administrative law systems demonstrates that modern rechtsstaat states preserve substantive justice through inclusive access to judicial review while enforcing robust procedural safeguards. The study concludes that targeted institutional reforms such as establishing an autonomous executorial agency, enacting contempt-of-court legislation, strengthening ombudsman oversight, and enhancing judicial education offer more constitutionally sound solutions to improve compliance with administrative court rulings. It further underscores the crucial role of rechtsvinding and proportionality in reconciling procedural limitations with constitutional mandates for substantive justice and legal certainty.